Structural Variations of the 3D Genome Architecture in Cervical Cancer Development - Adeel, Muhammad Muzammal; Jiang, Hao; Arega, Yibeltal; Cao, Kai; Lin, Da; Cao, Canhui; Cao, Gang; Wu, Peng; Li, Guoliang (Frontiers in Cell and Developmental Biology, 2021)
Human papillomavirus (HPV) integration is the major contributor to cervical cancer development by inducing structural variations (SVs) in the human genome. Structural Variations (SVs) are directly associated with the three-dimensional genome structure leading to cancer development. The detection of SVs is not a trivial task, and several genome-wide techniques have greatly helped in the identification of SVs in the cancerous genome. However, in cervical cancer, precise prediction of SVs mainly translocations and their effects on three-dimensional (3D)-genome and gene expression still need to be explored. Here, we have used high-throughput chromosome conformation capture (Hi-C) data of cervical cancer to detect the structural variations, especially the translocations and validated it through whole-genome sequencing (WGS) data. We found that the cervical cancer 3D-genome architecture rearranges itself as compared to that in the normal tissue, and 24% of the total genome switches their A/B compartments. Moreover, translocations detection from Hi-C data showed the presence of high-resolution t(4;7)(q13.1;q31.3) and t(1;16)(q21.2;q22.1) translocations, which disrupted the expression of the genes located at and nearby positions. Enrichment analysis suggested the disrupted genes were mainly involved in controlling cervical cancer-related pathways. In summary, we detect the novel SVs through Hi-C data and unfold the association among genome-reorganization, translocations and gene expression regulation. The results help understand the underlying pathogenicity mechanism of structural variations in cervical cancer development and identify the targeted therapeutics against cervical cancer.